In Silico and Validation Approaches for Optimum Conditions of Rattus norvegicus Target Gene qPCR Primers - Gracia Alice Victoria Pollo; Nyoman Yudi Antara; Firman Alamsyah; Rarastoeti Pratiwi (Journal of Tropical Biodiversity and Biotechnology, 2023)
The qPCR method requires an oligonucleotide pair to prime the amplification process. With the variety of qPCR reagent and primer options available, in silico and laboratory experimental validation approach was needed to validate the most suitable primer for prior use. This article aims to provide in silico analysis of actin alpha-2 smooth muscle (Acta2), fibroblast activation protein (Fap), hypoxanthine phosphoribosyltransferase-1 (Hprt1), platelet-derived growth factor subunit B (Pdgfb), phosphoinositide-3-kinase regulatory subunit-1 (Pik3r1), and vascular cell adhesion molecule-1 (Vcam1) qPCR primer with qPCR and electrophoresis validation. The procedure used in this approach was in silico analysis of primer from published articles and newly designed primer. The analysis was done with Primer-BLAST for gene specificity, Primer-Dimer, OligoCalc for hairpin formation, BLAST Nucleotide for identical sequence screening, and Clustal Omega for product length validation. Experimental validation was done using qPCR for optimal annealing temperature, priming ability, and amplificon specificity, and electrophoresis for product length validation. This assessment resulted in in silico and laboratory experimental validation of Acta2, Fap, Hprt1, Pdgfb, Pik3r1, and Vcam1 primer pairs producing suitable amplicon for qPCR using Rattus norvegicus cDNA with SYBR annealing temperature range of 60-65°C with three mM MgCl2. The primer pair can be used for further qPCR analysis under similar conditions and the procedure stated can be used as starting point for qPCR Primer preparation.